Organizational Sustainability Determinants in Different Cultural Settings: A Conceptual Framework. (16th January 2018) - Horak, Sven; Arya, Bindu; Ismail, Kiran M
Abstract: Since the link between organizations' sustainability initiatives and effects from the societal environment has not been consistently established in the literature, this paper provides a conceptual framework to demonstrate the antecedents to the levels of sustainability initiatives undertaken by firms. Taking insights from institutional theory, it proposes that the relationship between the sustainability determinants and the level of sustainability initiatives is mediated by coercive, mimetic and normative isomorphic pressures. Moreover, it suggests that culture plays a significant role in moderating the extent to which the various types of isomorphic pressure on firms may influence the levels of firms' sustainability initiatives. The implications of the framework are discussed in the light of encouraging sustainability initiatives and overall sustainable development in various cultural settings as well as undertaking future research to enhance the framework and its applicability. Copyright © 2018 John Wiley & Sons, Ltd and ERP Environment